2017
DOI: 10.1111/jcpe.12675
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in immune function (immune senescence) in caries and periodontal diseases: a systematic review

Abstract: Aim: To systematically review the evidence regarding immune senescence in the pathogenesis of periodontitis and dental caries. Methods: A systematic search of electronic databases utilizing medical subject headings (MeSH terms) supplemented by screening of review articles and other relevant texts was undertaken. Results: Seventy-three articles were included (43 for periodontitis, 30 for caries). Study results were found to be generally heterogeneous. Regarding periodontitis, human studies suggest evidence for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
64
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 98 publications
5
64
0
1
Order By: Relevance
“…The influence of ageing on periodontitis is complex, but has been suggested to be related to an accumulated exposure of the disease rather than increasing susceptibility. However, altering immune functioning: immune senescence, associated with ageing has been suggested as a plausible biological mechanism that may affect the susceptibility to periodontitis among elderly (Preshaw, Henne, Taylor, Valentine, & Conrads, ). Another hypothesis that may explain an increased susceptibility to periodontitis relates to changes in proliferative capabilities of cells and reduced wound healing capacity through a decrease in type I collagen (Caceres, Oyarzun, & Smith, ; Hajishengallis, ; Lim, Liu, Mah, Chen, & Helms, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of ageing on periodontitis is complex, but has been suggested to be related to an accumulated exposure of the disease rather than increasing susceptibility. However, altering immune functioning: immune senescence, associated with ageing has been suggested as a plausible biological mechanism that may affect the susceptibility to periodontitis among elderly (Preshaw, Henne, Taylor, Valentine, & Conrads, ). Another hypothesis that may explain an increased susceptibility to periodontitis relates to changes in proliferative capabilities of cells and reduced wound healing capacity through a decrease in type I collagen (Caceres, Oyarzun, & Smith, ; Hajishengallis, ; Lim, Liu, Mah, Chen, & Helms, ).…”
Section: Introductionmentioning
confidence: 99%
“…Henne, Taylor, Valentine, & Conrads, 2017). Another hypothesis that may explain an increased susceptibility to periodontitis relates to changes in proliferative capabilities of cells and reduced wound healing capacity through a decrease in type I collagen (Caceres, Oyarzun, & Smith, 2014;Hajishengallis, 2010;Lim, Liu, Mah, Chen, & Helms, 2014).…”
mentioning
confidence: 99%
“…Finally, noise stress may generate reactive oxygen species and proinflammatory cells, which are involved in inflammation and degradation of the extracellular matrix and connective tissue . Similar immunological mechanisms are involved in the pathogenesis of periodontitis through poor oral hygiene, reduced immune function, and insulin resistance . In addition, previous authors have suggested that a noisy environment reflects a low sociodemographic environment, which is linked to health problems …”
Section: Introductionmentioning
confidence: 99%
“…При этом имеются только единичные исследования, посвященные местным факторам иммунной защиты [6][7][8]. Мониторинговые исследования по изучению сравнительной характеристики местного иммунного статуса при дентальной имплантации практически отсутствуют, а имеющиеся работы выполнены преимущественно в эксперименте на животных [9][10][11], что определило выбор направления наших исследований.…”
unclassified